Sensibilidade de Phakopsora pachyrhizi a fungicidas, lixiviação pela chuva, volume de calda e tamanho de gota no controle da ferrugem em soja - Chechi, Amanda (2019)
Asian soybean rust (ASR), caused by the fungus Phakopsora pachyrhizi, is one of the most severe diseases affecting the crop and the main control strategy is the fungicide application. Factors such as spray volume, droplet size, product features, the soybean cultivar used, and also the climatic conditions, such as the rain occurrence, influence the disease control effectiveness. The objectives of this work were to evaluate the sensitivity of twelve P. pachyrhizi isolates to the most commonly used fungicides; to verify if the rainfall simulation, at different time intervals (30 to 240 minutes), after the application of penetrant and non-penetrant fungicides with different spray volumes (70 and 150 L ha -1 ), affects the effectiveness of the ASR chemical control; and to verify if the combination of spray volumes (70, 110 and 150 L ha -1 ) and droplet sizes (fine and medium), in the fungicide application in the field, affects the ASR control in soybean cultivars with different leaf area index (BMX Lança and BMX Garra). As a result of the first assay, the fungicides presented different levels of fungitoxicity to P. pachyrhizi isolates obtained from different places. Site-specific fungicides showed high to moderate fungitoxicity to the isolates while the multisites presented moderate to slightly toxic activity. For the rain simulation test, non-penetrating fungicides were more susceptible to rain removal, especially when using the 70 L ha -1 spray volume. The control percentages of the treatments were considered statistically similar to the control which received the fungicide application but it was not submitted to rainfall, when it occurred between 120 and 180 minutes after the application of penetrating fungicides and at 240 minutes for the non-penetrants. The closer is the application of the fungicide to the rain occurence, the greater are the product removal and the disease control reduction. Non-penetrating fungicides were more susceptible to leaching than penetrants. The spray volume of 150 L ha -1 attenuated in one hour the rain impact on the fungicide absorption or retention on the leaf surface, promoting greater disease control. For the last trial, increasing spray volumes according to the crop development (70, 110 and 150 L ha -1 ) and fine droplets (in the second and third applications) showed yield results similar to the use of 150 L ha -1 fixed spray volume, regardless of droplet size, for cv. BMX Lança in 2017, when its maximum leaf area index (LAI) was 5.8. For cv. BMX Garra, which in the same year presented maximum LAI of 7.1, the highest seed yield was observed with the use of the fixed spray volume of 150 L ha -1 in all applications, with both droplet sizes. In 2018, cultivars BMX Lança and BMX Garra had maximum LAI of 4.9 and 5.5, respectively, and no statistical differences were detected among the treatments that received fungicide application. The exception was only the treatment with 70 L ha -1 in all applications, with medium drops for cv. Garra, which was statistically inferior when compared to the other treatments. The higher the leaf area index and the disease pressure, the greater is the need of soybean plants protection, and the use of larger spray volumes promotes greater leaf area protection and fine droplets presented greater capacity to penetrate along the soybean canopy, providing greater target coverage.